PEMBELAJARAN BERBASIS EDUTAINMENT PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SD NEGERI 1 KEMBARAN KULON PURBALINGGA - Yamni Yunus (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
Islamic Religious and Character Education is a very essential lesson at all levels of education. Ideally, a lesson can increase students’ motivation to learn. However, the learning carried out so far tends to be boring, so creative and innovative learnings are needed. One of them is edutainment, a learning process designed in such a way in which educational material and entertainment are integrated harmoniously to create fun, comfortable, and conducive learning. At SD Negeri 1 Kembaran Kulon Purbalingga, teachers have implemented edutainment in the subject of Islamic Religious Education and Character Education through welcoming students every morning, praying dhuha and dhuhur in congregation, routine memorization, and learning recitation with nature.